Respuesta :
Answer: 2.88 or 0.116
Step-by-step explanation:
use the formula: (-b+-√b² - 4 * a * c ) / 2a
here b = -9 , a = 3 , c = 1
so putting the values in our equation,
--9-√(- 9)²-4 * 3 * 1 / 2 * 3 or --9-√(- 9)²-4 * 3 * 1 / 2 * 3
Answer in fraction : (9 +√69 ) / 6 or (9 -√69 )
Answer in decimals : 2.88 or 0.116
It should be 3x^2-9x+1=0
[tex]\\ \sf\longmapsto x=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]
[tex]\\ \sf\longmapsto x=\dfrac{9\pm\sqrt{81-12}}{2(3)}[/tex]
[tex]\\ \sf\longmapsto x=\sqrt{9\pm\sqrt{69}}{6}[/tex]